All serotypes of dengue virus induce HLA-A2 major histocompatibility complex class I promoter activity in human liver cells - Othman, S.; Rahman, N.A.; Yusof, R. (2010)
In contrast to many viruses that escape the host's immune responses by suppressing the major histocompatibility complex (MHC) class I pathway, flaviviruses have been shown to up-regulate the cell surface expression of MHC class I complex. The mechanism by which dengue virus (DV) achieves this up-regulation remains unclear. Our investigation on the HLA-A2 gene in human liver cells demonstrated that all four serotypes of dengue virus, DV1 to DV4, resulted in variable degrees of promoter induction. This illustrates the importance of MHC class I transcription regulation in primary infections by different DV serotypes that may have even greater impact in secondary infections, associated with increased disease severity. (C) 2010 Royal Society of Tropical Medicine and Hygiene. Published by Elsevier Ltd. All rights reserved.